Analyzing Tai Chi Promotion and Tai Chi Physical Education Teacher Educati - Wang, Yanlin (The Journal of the International Society of Chinese Health Practices, 2024)
Abstract:Tai Chi is a national intangible cultural heritage, which is the essence of Chinese excellent traditional culture. It is a traditional Chinese boxing art that takes the dialectical concepts of taiji and yin and yang in the traditional Chinese philosophy of Confucianism and Taoism as the core idea, and combines various functions such as strengthening the body and cultivating the mind and body, and is good for the internal and external cultivation of human beings. Since 2020, when Tai Chi was formally inscribed on UNESCO's Representative List of Intangible Cultural Heritage of Humanity, China's attention to Tai Chi has been increasing year by year, and the inheritance and promotion of Tai Chi has also shown a positive trend, while the education of Tai Chi has also received more and more attention. Strong education must first strengthen teachers, and a strong education country is an important guarantee for realizing the great rejuvenation of the Chinese nation. General Secretary Xi Jinping put forward "Solidly Promoting the Construction of a Strong Education Nation" in the fifth collective study of the Politburo of the Central Committee, which emphasized the need to cultivate high-quality teacher teams. The quality and standard of the teacher team largely affects the students' thinking and behavioral performance. At present, the construction of the Tai Chi physical education teacher team in China's colleges and universities is still characterized by an incomplete system and inadequate legal protection, and there is a need to further improve the system of education for physical education teachers with Chinese characteristics, in particular, to strengthen the pre-service and on-the-job education of physical education teachers, so that the physical education teachers will have transversal knowledge of the subject and more comprehensive professional technical It is necessary to further improve the education system of physical education teachers with Chinese characteristics, especially to strengthen the pre-service and in-service education of physical education teachers, so that physical education teachers can have knowledge of horizontal disciplines and more comprehensive professional and technical skills, and thus build a high-level and high-quality physical education team. 1.The research purpose of this paper is to put forward rationalization suggestions for promoting the construction of Tai Chi physical education teacher team at the theoretical level, and then to provide useful reference for the effective promotion of the intangible cultural heritage of mankind,Tai Chi. 2.The research methods used in this paper: mainly literature method, expert interview method, and logical analysis. By reviewing a large number of domestic and foreign literature and materials related to pre-service education, physical education, sports health, aerobic control training, etc. on websites such as Knowledge.com, Wan fang, EBSCO, Web of Science, etc., according to the purpose and task of this study, we communicate and study with experts in physical education and training, national traditional sports, etc., to learn about the teaching methods for Tai Chi education,the construction of teachers' team, and the precautions for physical education teaching. 3. The research results of this paper: (1) The teaching design of Tai Chi is single, the teaching objectives, teaching content and teaching evaluation are set in stone, since Tai Chi course entered colleges and universities, the teaching objectives are only focused on the teaching of students' movements and routines, and the education of students' emotions, attitudes, and values has been ignored; the teaching content is basically fixed as 24 simplified Tai Chi, but in fact, there are many kinds of Tai Chi boxing methods, which can not be summarized by 24 simple movements. The teaching content is basically fixed to 24 simplified Tai Chi, but in fact, Tai Chi has many kinds of boxing styles, which can be summarized by more than 24 simple movements. Simple "manipulation" of Tai Chi will make the students less active in practicing Tai Chi and even wushu; in terms of teaching evaluation, the emphasis on summative evaluation and neglect of the process of evaluation are not conducive to the promotion and development of Tai Chi. Therefore, it is necessary to improve the curriculum system of Tai Chi, improve the practicality of technical movements, combine the theoretical value of Tai Chi with its practical value, and make students understand the offensive and defensive nature of Tai Chi, so as to help them protect themselves at critical moments.(2) Tai Chi teachers' professionalism is generally low. Tai Chi is one of the physical education courses in the general education courses for college students, but most of the teachers in the majority of colleges and universities do not have a martial arts background, do not have a high degree of grasp of the precision of movement teaching, do not have the technical skills of teachers who have a professional martial arts background and have a low reserve of professional knowledge of Tai Chi, which leads to a poor understanding of Tai Chi culture among students and a weak ability to combine the theory and the practice. As a result, students do not have a deep understanding of Tai Chi culture, and their ability to combine theory and practice is weak. In view of the above problems, schools can improve the teaching quality and teaching ability of physical education teachers through the introduction of special talents in Wu shu, in-service or on-the-job education for physical education teachers in colleges and universities or those who are about to be recruited, and carry out Tai Chi teaching competitions to promote the high-quality development of Tai Chi teaching.(3) Teaching qualification of Tai Chi teachers is ill-defined. Teaching qualification of Tai Chi teaching is the main problem of Tai Chi teaching in schools at present, and many Tai Chi teachers of university general education have superficial knowledge of Tai Chi movements, and the accuracy of the movements is low, which is not conducive to the students' mastery of Tai Chi and its connotations. In this regard, the state should introduce corresponding policies to certify the qualification of Tai Chi teachers, improve the standard and quality of Tai Chi teaching, andprovide policy support and guarantee for the high-quality development of Tai Chi. 4.The research conclusion of this paper: At present, there are still problems in Tai Chi physical education teaching, such as single teaching design, low professionalism of teachers, and unclear definition of teacher teaching qualifications. It is urgent to take corresponding measures, such as establishing a sound Tai Chi teaching system, cultivating professional Tai Chi teachers, improving the Tai Chi teacher qualification certification system, so that students can better understand and master the connotation of Tai Chi technical movements in physical education classrooms, and promote their physical and mental harmonious development.